On some generalizations of Nadler's contraction principle - COROIAN, Iulia (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The purpose of this work is to present some generalizations of the well known Nadler's contraction principle. More precisely, using an axiomatic approach of the Pompeiu-Hausdor_ metric we will study the properties of the fractal operator generated by a multivalued contraction. Mathematics Subject Classification (2010): 47H25, 54H10.